Pop The Hood! With Flaps To Lift - Hechtenkopf, Omar; Nickelodeon (Firm) (New York, NY : Random House Children's Books, a division of Penguin Random House LLC, 2016)
"The monster machines need repairs, but Gabby's toolbox is missing. Lift the flaps to help Blaze save the day and get his friends running again!"--back cover.
"With flaps to lift!"--Cover.
new kids book 2023 winter.
Keywords: Toolboxes; Tucks (Sewing); Transportation; Concepts